PERTANGGUNGJAWABAN PIDANA OLEH PARTAI POLITIK TERHADAP EKSEKUSI UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI DAN PENCUCIAN UANG - Raka Devara Putrawicaksana (2022)
The purpose of writing this scientific work is to find out the urgency of accountability for the policy of execution of substitute money in corruption cases and to know how ideally to regulate accountability for the execution of substitute money in corruption cases in the future. The research method used is normative juridical. In the event that criminal liability related to money can be charged to a political party, it can be categorized as a corporation based on the definitions of political parties and corporations as stated in Law Number 31 of 1999 as amended in Law Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption and Law Number 2 of 2008 as amended in Law No. 2 of 2011 concerning Political Parties, but in reality on the ground there are no political parties that have been subject to criminal responsibility for crimes of corruption committed by their members or administrators even though the politics received funds from the proceeds of corruption. Thus, it is necessary to have regulations that accommodate the imposition of substitute money for corruption and money laundering.